A comparative analysis of cost efficiency and its determinants for public-listed port operators in Malaysia / Mariam Mahmun - Mahmun, Mariam (2021)
The Investment in port infrastructure is not only costly in nature but its return on investment takes much longer. In view of its capital intensity, port efficiency is not just about measuring output performance, but it is also important in ensuring business sustainability. Rapid changes in the global shipping environment and intensified competition in the port industry have pressured ports to upgrade their costly infrastructure, particularly to meet the increasing demands of shipping liners in order to remain competitive. The objective of this study is two-fold. First, this study aims to examine the cost-efficiency of Malaysian ports operated by public-listed companies in the country. Secondly, the study aims to determine the relationship between selected factors in influencing the cost-efficiency of the ports. This study employed a quantitative method which combined data envelopment analysis (DEA) estimation to measure the level of cost-efficiency of each operator and a regression model to determine the relationships between ownership, environmental commitment, competition, gross domestic product and the cost-efficiency score. Data were collected from four companies’ annual reports for the period of 2011 until 2019. The findings from the study based on the implemented models indicate that the ports are operating at different efficiency levels but generally below the full efficiency. The ranking of cost-efficiency by operators are also identified. Competition has positive relationship in influencing the cost-efficiency of these ports. Meanwhile, GDP growth and ownership of ports had positive relationship but not significant to determine level of cost efficiency whereas environmental commitment has inverse relationship but significant to cost efficiency. Findings from the current work contribute to the body of knowledge with regard to the field of port efficiency in Malaysia. The outcomes from this study are useful for policy makers in determining appropriate policies to encourage operators to rationalise resources and support the growth of ports in the country. The study also provides significant inputs to Malaysian port operators in observing causes of inefficiency and to help them improve their operational and financial strength. Investors including shareholders could then evaluate returns to their share investment values in the company and demand on improvements in port efficiency.